Because it is my blood - Zevin, Gabrielle (Zevin, Gabrielle. Birthright, 2012)
In 2083, seventeen-year-old Anya Balanchine seeks a way to make Balanchine Chocolate legitimate, and although a trip to Mexico gives her new insights and ideas, escaping her mobster family's legacy of violence may prove impossible.